Promising approaches to improve the performances of hybrid non‐isocyanate polyurethane. Issue 4 (3rd January 2019) - Ke, Jiexi; Li, Xiaoyun; Jiang, Shuai; Liang, Chen; Wang, Junwei; Kang, Maoqing; Li, Qifeng; Zhao, Yuhua
Abstract: The performances of hybrid non‐isocyanate polyurethane (NIPU) materials were improved by using promising approaches. For the ring‐opening reaction of cyclic carbonate with excess amine, methanol was selected as solvent to increase the molar mass of NH2 ‐terminated NIPU pre‐polymer but also caused the formation of urea as a result of eliminating hydrogen bonding between NIPU chains. Meanwhile, another approach was carried out to reduce the content of urea by altering the introduction mode of reactants, along with further increasing the molar mass of the NIPU pre‐polymer. The final hybrid materials were prepared by adding bisphenol‐A diglycidyl ether into the pre‐polymer. The results indicated that the introduction of methanol and the change of the introduction mode of reactants could improve the performance of the hybrid materials. The hybrid material derived from the forward method has optimal performance with a tensile strength of 10.8 MPa, elongation at break of 167%, a glass transition temperature of 49.1 °C and a crosslinking density of 450 mol m −3 as well as presentable thermodynamic stability, ascribed to the high molar mass of the NIPU pre‐polymer, the low urea content and the dense crosslinking network. © 2018 Society of Chemical Industry Abstract : The effect of hydrogen bonding and introduction mode of reactants on modifying performances of hybrid non‐isocyanate polyurethane was investigated.